2001
DOI: 10.1080/03768350123961
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative determination of the food security status of rural farming households in the Northern Province of South Africa

Abstract: The majority of South Africans living in rural areas are food insecure despite high levels of national food self-sufficiency. The household food security position of two groups of rural farming households in the Venda region was evaluated quantitatively: one group produces vegetables that are sold or consumed locally, the other group produces cash crops - mangoes and other subtropical fruits. Using the collected data, food availability and energy, protein and fat requirements were calculated and balances deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…A MAHFP score was calculated which ranges from 0 to 12 (Swindale and Bilinsky 2007). & While it is not a direct measure of food insecurity, share of food in the total household expenditure was calculated (Leroy et al 2001). Food expenditure was computed by summing the expenditure on all individual food items bought in 1 month.…”
Section: Methodsmentioning
confidence: 99%
“…A MAHFP score was calculated which ranges from 0 to 12 (Swindale and Bilinsky 2007). & While it is not a direct measure of food insecurity, share of food in the total household expenditure was calculated (Leroy et al 2001). Food expenditure was computed by summing the expenditure on all individual food items bought in 1 month.…”
Section: Methodsmentioning
confidence: 99%
“…In 1999, the level of stunting among children in Limpopo Province (23.1%) was representative of that in the nation as a whole (23.8%) [8]. In their study of food security in rural farming households in northeastern Limpopo Province, Leroy et al [9] found that more than 80% of households had a negative balance of energy, protein, and fat intake.…”
Section: Introductionmentioning
confidence: 99%
“…A sampling approach similar to the rotating bi-annual Labour Force Survey was recommended using sentinel sites. Mekuria & Moletsane (1996) and Leroy et al (2001) conducted two small studies of household food security in the Limpopo Province. Mekuria & Moletsane (1996) surveyed 197 randomly selected households from five districts in the Limpopo Province.…”
Section: Aliber and Modisellementioning
confidence: 99%
“…Coping strategies commonly employed by the sample households in the face of food insecurity were: dependence on community/social networks, own food production, seeking employment, and asset accumulation. Leroy et al (2001) applied a formal, structured questionnaire to 52 farmers in the Venda region. Survey data was verified through informal surveys.…”
Section: Aliber and Modisellementioning
confidence: 99%